Angst vor den Nachbarn
This broadcast focuses on Macedonia, the former republic of Yugoslavia, and its new-found independence. President Kiro Gligorov is interviewed throughout the report, discussing international recognition of Macedonia. The dispute between the Macedonian government and Greece is also highlighted, describing how each have claim laid to the title of Macedonia. The tension between ethnic Albanians and Macedonians is also discussed. The economic crisis in the region is explained, showing how Macedonia is ineligible for aid from international organizations because, as of this report, it had not yet been internationally recognized.